2015
DOI: 10.1002/mgg3.180
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of the Melanocortin 4 receptor (MC4R) gene in a South African study group

Abstract: Obesity is a global epidemic that results in significant morbidity and mortality. Mutations in the melanocortin 4 receptor (MC4R) gene, which codes for a G‐protein‐coupled receptor responsible for postprandial satiety signaling, have been associated with monogenic obesity. The prevalence of obesity is on the increase in South Africa, and it is hypothesized that mutations in MC4R are a contributing factor. The aim of this study was to perform a retrospective assessment of the relationship between allelic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…We found that none of the metabolic GRSs were significantly associated with obesity-related traits in the Ghanaian population, which contradicts the findings of the previous GRS-related studies in European and African populations [15,[25][26][27][28][29][30]32,33]. Efforts to replicate previously reported genetic associations of individual SNPs with obesity measures in non-African populations have shown limited success among Africans [23,31,51,52], which is also in line with the findings from the present study. Several factors are likely to be involved in such discrepancies between our findings and genetic association studies in Europeans.…”
Section: Discussioncontrasting
confidence: 52%
“…We found that none of the metabolic GRSs were significantly associated with obesity-related traits in the Ghanaian population, which contradicts the findings of the previous GRS-related studies in European and African populations [15,[25][26][27][28][29][30]32,33]. Efforts to replicate previously reported genetic associations of individual SNPs with obesity measures in non-African populations have shown limited success among Africans [23,31,51,52], which is also in line with the findings from the present study. Several factors are likely to be involved in such discrepancies between our findings and genetic association studies in Europeans.…”
Section: Discussioncontrasting
confidence: 52%
“…Epidemiologic data have estimated that 0.05% individuals have variations in MC4R in general population 16,17. Furthermore, the prevalence of MC4R variants in adult with obesity is 0.2% and ~5%–6% in patients with severe early-onset obesity 18,19.…”
Section: Introductionmentioning
confidence: 99%
“…While the obesity epidemic has disproportionately affected non-Hispanic African-American and Hispanic youth in the United States (6), little is known about the prevalence of MC4R mutations in children of these ethnicities. In a recently published study of 25 unrelated Afro-Caribbean children with obesity from the Guadeloupe Island, one 11.8 year-old boy had a p. Ile301Thr mutation in MC4R (7), while in a study of South African adults of mixed ancestry that included 63% Black Africans (n = 187), 2.6% harbored a rare MC4R variant (8). These studies provide early clues on the expected prevalence of MC4R variants in children of non-European ancestry.…”
Section: Introductionmentioning
confidence: 86%